Earthquake clustering analysis in North Sumatra region based on double-difference relocation - Purba, Rini Kumala Sari; Aisjah, Aulia Siti; Arifin, Syamsul; Nugroho, Hendro (Jurusan Pendidikan Geografi Universitas Negeri Manado, 2025)
North Sumatra is an active tectonic zone influenced by the complex interaction between the subduction of the Indo-Australian plate and the movement of the Sumatra Fault. Accurate determination of earthquake hypocenter locations is crucial for seismotectonic modeling and disaster mitigation. This study aims to improve the precision of earthquake hypocenter location in this region through the implementation of the Double-Difference (HypoDD) relocation method and to analyze clustering based on the spatial distribution of earthquakes to identify active fault segments. The earthquake data used came from local seismic station catalogs during the period 2008–2024. The application of the HypoDD method significantly reduced the Root Mean Square (RMS) value of the average seismic phase arrival residual from 0.79373 to 0.33888, indicating an increase in the accuracy of the hypocenter location. Earthquake clustering analysis identified a total of 10 clusters that showed a strong correlation with the surrounding geological structure. The shallow earthquake cluster in the Tarutung region was dominated by a strike-slip fault mechanism, which definitively confirmed that the Renun Segment is an active segment of the Sumatra Fault with intense activity. In addition, a swarm pattern with low magnitude and very shallow depth (<15 km) was identified in the Toba Basin (Cluster 2), indicating the contribution of tectonic-magmatic processes. The cluster of medium- to deep-depth earthquakes (70–150 km) is strongly associated with subduction activity in the Sumatra intraslab megathrust zone. Overall, this study successfully mapped the spatial distribution pattern of earthquake sources in greater detail, contributing significantly to the updating of earthquake hazard maps and the determination of active fault zones in North Sumatra.